Elastic Wave Behaviour in 2-D Acoustic Interface Superlattices of an Altered Phase - KAPELEWSKI, Jerzy; LILA, Bogdan (Archives of Acoustics, 2011)
The purpose of the paper is to outline a systematic and unified non-local treat-ment of mode conversion effects associated with an interface superlattice being a 2Dpseudo-array composed of altered phase inclusions (exemplified by impurity clusters)and located at a solid-solid plane interface. It will be illustrated, in some detail, forthe instructive case of a Stoneley type acoustic wave (SW), incident on a period-ically nonhomogeneous portion of an interface and partly transformed into bulkmodes propagating in one of the component solid. An analytical model scheme isconstructed, using a variational method combined with the T matrix approach, ap-propriate for the 2D periodic array treated, and decaying into the depth of this solidfor the structure in a way determined by the array geometry and element 3D pro-files as well as the boundary conditions at the interface. An apodization (weighting)to reduce the side-lobes level is incorporated into the structure by appropriatelyvarying lateral dimensions and the depth of particular scatterers.